2018
DOI: 10.1016/j.cellsig.2018.06.005
|View full text |Cite|
|
Sign up to set email alerts
|

Role of cAMP and phosphodiesterase signaling in liver health and disease

Abstract: Liver disease is a significant health problem worldwide with mortality reaching around 2 million deaths a year. Non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) are the major causes of chronic liver disease. Pathologically, NAFLD and ALD share similar patterns of hepatic disorders ranging from simple steatosis to steatohepatitis, fibrosis and cirrhosis. It is becoming increasingly important to identify new pharmacological targets, given that there is no FDA-approved therapy yet for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 179 publications
(178 reference statements)
2
83
0
1
Order By: Relevance
“…These findings are significant because cAMP signaling is very important for the liver and inadequate cAMP levels would compromise normal functioning of the liver. (8) Indeed, the present in vivo and in vitro studies demonstrated that the ethanolmediated decrease in cAMP signaling predisposes hepatocytes to increased ER stress and apoptosis.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These findings are significant because cAMP signaling is very important for the liver and inadequate cAMP levels would compromise normal functioning of the liver. (8) Indeed, the present in vivo and in vitro studies demonstrated that the ethanolmediated decrease in cAMP signaling predisposes hepatocytes to increased ER stress and apoptosis.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, hepatocytes of patients with AH had much greater immune‐reactivity for all three PDE4s, which implicates PDE4 as a likely source of dysregulated cAMP signaling in livers from patients with AH. These findings are significant because cAMP signaling is very important for the liver and inadequate cAMP levels would compromise normal functioning of the liver . Indeed, the present in vivo and in vitro studies demonstrated that the ethanol‐mediated decrease in cAMP signaling predisposes hepatocytes to increased ER stress and apoptosis.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Epinephrine increases hepatic glycogenolysis and HGP in a cAMP-PKA-dependent pathway (Bousquet-MĂŠlou, Galitzky, Moreno, Berlan, & Lafontan, 1995;Kolnes et al, 2015;Wasserman & Cherrington, 1991). Phosphodiesterase 3B and 4B (PDE3B, PDE4B) are the primary enzymes responsible for the degradation of cAMP in the liver (Avila, Barker, Zhang, McClain, & Barve, 2016;Berger et al, 2009;Omori & Kotera, 2007;Wahlang, McClain, Barve, & Gobejishvili, 2018). Therefore, in order to determine if epinephrine responsiveness was associated with changes in phosphodiesterase expression, we measured Pde3b and Pde4b gene expression in the liver.…”
Section: Pde3b and Pde4b In Liver Are Increased With Exercise Trainingmentioning
confidence: 99%